A systematic review of published evidence on intervention impact on condom use in sub-Saharan Africa and Asia. Issue 7 (11th October 2007) - Foss, A M; Hossain, M; Vickerman, P T; Watts, C H
Abstract : Objective: There has been much debate about the value of condoms in HIV/STI programming. This should be informed by evidence about intervention impact on condom use, but there is limited compiled literature. This review aims to quantify intervention impact on condom use in sub-Saharan Africa and Asia, in different types of partnership. Methods: A systematic review was conducted of papers published between 1998 and 2006 presenting evaluations of interventions involving condom promotion in sub-Saharan Africa and Asia. Data on reported postintervention levels of condom use, and various measures of changes in condom use, by partnership type, were compiled. Results: A total of 1374 abstracts were identified. Sixty-two met the inclusion criteria (42 reporting significant increases in condom use): 44 from sub-Saharan Africa and 18 from Asia. Many (19) reported on condom use in commercial sex (15 significant), six on use with casual partners (three significant), 11 on use in marital/steady partnerships (nine significant), 14 on use by youths (eight significant) and 20 combined partnership types (11 significant). There is substantial evidence of interventions targeted at sex workers and clients achieving large increases in condom use. Far less evidence exists of intervention impact on condom use in casual relationships. In primary partnerships, postintervention condom use was low unless one partner was knowingly HIV-infected or at high-risk, or avoiding pregnancy. Evaluations of interventions targeting youths recorded limited increases in condom use. Conclusions: The findings illustrate the range of evidence about postintervention condom use in different partnerships, and how patterns of use are influenced by partnership type and perceptions of risk. Where possible, intervention studies should also assess biological endpoints, since prevention of infection is the measure of most interest in the evaluation of condom promotion interventions.